P431Evaluation of tpe-te interval and tpe-te/QTc ratio in patients with coronary artery ectasia. (15th July 2014) - Karaagac, K; Yontar, O C; Tenekecioglu, E; Vatansever, F; Arican Ozluk, O; Tutuncu, A; Yagcioglu, P; Yilmaz, M
Abstract: Aim: Coronary artery ectasia (CAE) is commonly defined as local or generalized dilatation of a coronary vessel up to 1, 5 times the diameter of an adjacent vessel. Tp-Te interval and Tp-Te/QT ratio have emerged as a novel electrocardiographic (ECG) markers of increased dispersion of ventricular repolarization. The aim of this study was to evaluate ventricular repolarization by using Tp-Te interval and Tp-Te/QT ratio in patients with CAE. Materials and methods: Patient records were retrospectively analyzed. ECG of 28 patients, who were diagnosed as CAE were obtained and scanned.Tp-Te, QT and corrected QT intervals and some other ECG intervals were measured. ECGs of age and sex matched 22 healthy control individuals were also analyzed for comparison. Results: Baseline characteristics and QT, QTc intervals were similar in both group. Tp-Te (97, 71±8, 7 vs 85, 23±7, 1; p<0, 001) and Tp-Te/QT (0, 22±0, 0 vs 0, 20±0, 0; p<0, 001) were significantly worse in CAE group. Conclusions: :Tp-Te is a measure of transmural dispersion of repolarization in the left ventricle and accepted as a surrogate for increased ventricular arrhythmogenesis risk. Tp-Te and Tp-Te/QT are relatively new markers which also indicate repolarization defects. Our results show that CAE patients significantly higher values of Tp-Te and Tp-Te/QT than controls. These measurements may indicate increased arrhythmogenesis risk for individuals with CAE. Parameters Patients Controls p value LVEDD (mm) 45±8 43±10 0.59 LVESD (mm) 28±5 26±6 0.48 LVEF (%) 62.9±4.4 65.9±5.1 0.03 QT max 383.43±30 375.91±23 0.35 QTc max 421.32±26 409.95±18 0.09 TPe 97.71±8.7 85.23±7.1 <0.001 TPe/QT ratio 0.22±0.0 0.20±0.0 <0.001 QT disp 26.89±9.9 24.41±6.5 0.31 Echocardiographic and electrocardiographic parameters between the patient group with the control group.